2019
DOI: 10.1002/ece3.5187
|View full text |Cite
|
Sign up to set email alerts
|

Genomic signatures of adaptation to Sahelian and Soudanian climates in sorghum landraces of Senegal

Abstract: Uncovering the genomic basis of climate adaptation in traditional crop varieties can provide insight into plant evolution and facilitate breeding for climate resilience. In the African cereal sorghum (Sorghum bicolor L. [Moench]), the genomic basis of adaptation to the semiarid Sahelian zone versus the subhumid Soudanian zone is largely unknown. To address this issue, we characterized a large panel of 421 georeferenced sorghum landrace accessions from Senegal and adjacent locations at 213,916 single‐nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 85 publications
(144 reference statements)
4
40
3
Order By: Relevance
“…Previous studies showed that core collections based on either genotypic profiles or random selection could represent the genetic diversity of the entire collection [3]. The number of rare alleles (MAF < 0.05) in the Sudan core set (22%) was lower than that observed in the NPGS Ethiopia core set (60% [22]; and NPGS Senegal collection (32% [40];. Thus, the high frequency of the Durra genetic background and high frequency of rare alleles in Sudanese populations 1 and 2 suggests that both of these populations originated from Ethiopia.…”
Section: Preservation Of Npgs Sudan Core Collectionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies showed that core collections based on either genotypic profiles or random selection could represent the genetic diversity of the entire collection [3]. The number of rare alleles (MAF < 0.05) in the Sudan core set (22%) was lower than that observed in the NPGS Ethiopia core set (60% [22]; and NPGS Senegal collection (32% [40];. Thus, the high frequency of the Durra genetic background and high frequency of rare alleles in Sudanese populations 1 and 2 suggests that both of these populations originated from Ethiopia.…”
Section: Preservation Of Npgs Sudan Core Collectionmentioning
confidence: 92%
“…Genome scans based on nucleotide polymorphism pattern, environmental variables, selection signature, and candidate gene approach may provide insights into the genetic control of these traits in the Sudanese germplasm [47]. For instance, variation in the photoperiod sensitivity and panicle compactness of the NPGS Senegal collection was associated with several known sorghum genes [40]. Allele frequency distribution of the SNP S4_ 62,316,207 located in the Tan1 gene (Sobic.004 g280800 [48]; indicated that genetic variation was limited to the Sudanese populations 1 and 2.…”
Section: Genome-wide Association Study In Npgs Sudan Core Collectionmentioning
confidence: 99%
“…Genetic diversity and structure of the WASAP were compared with the global diversity panel (GDP) that consists of 692 worldwide sorghum accessions (excluding accessions from Americas) with available sequencing data, including West African accessions in the GDP (hereafter named WAS-GDP) (Morris et al , 2013;Lasky et al , 2015). WASAP accessions were also compared to previously genotyped West African accessions from USDA-GRIN (hereafter named WAS-GRIN), originating from Niger (NiGRIN), Senegal (SnGRIN; including a few accessions from neighboring Gambia and Mauritania), and Nigeria (NGrGRIN) Olatoye et al , 2018;Faye et al , 2019).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Background effect was accounted for using ADMIXTURE ancestry fractions used as fixed effect covariates. Candidate gene colocalization with QTL was carried out using an a priori candidate genes/loci list, including known sorghum genes and orthologs of rice and maize for adaptive traits, previously described (Faye et al , 2019). The Sorghum QTL Atlas (Mace et al , 2019) was used to compare QTLs identified in the current study to QTLs from previous studies.…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%
See 1 more Smart Citation